Some characteristics of hospital associated infections manifesting in patterns and the knowledge, attitudes and practices of nurses on hospital associated infections in the Intensive Care Units of the National Hospital of Sri Lanka - Ranaweera, A.D (My University, 2007)
The study was carried out in ten ICUs of the NHSL during a period of 3 months. Estimated sample size for the part I of the study was 320. All patients in the ICUs who had completed 2 days after hospital admission and, admitted during the study period were enrolled in to the study using the consecutive sampling technique. All the nurses attached to ten ICUs in the NHSL